Polymer-Engineered Interfaces for Tailoring Resistive Switching in TiO2-Based Memristors - Thien, Gregory Soon How; Wong, Yee-Jet; Tan, Kar Ban; Murthy, H.C. Ananda; Surendra, B S; Chan, Kah-Yoong (Engineering, Technology & Applied Science Research, 2026)
Resistive Random-Access Memory (ReRAM) devices constitute a popular Non-Volatile Memory (NVM) solution. Nevertheless, TiO2-based memristors suffer from instability and low endurance, with the effect of Polymethyl Methacrylate (PMMA) polymer on improving these limitations being unexplored. This study examines the interfacial positioning of PMMA polymeric layers within TiO2-based memristors. Four device structures were initially fabricated to analyze the effects of PMMA interfacial positioning on several Resistive Switching (RS) parameters using Fluorine-doped Tin Oxide (FTO) and Carbon (C) electrodes: (i) FTO/TiO2/C, (ii) FTO/TiO2/PMMA/C, (iii) FTO/PMMA/TiO2/C, and (iv) FTO/PMMA/TiO2/PMMA/C. Only FTO/TiO2/PMMA/C and FTO/PMMA/TiO2/C demonstrated clear bipolar RS behavior. The FTO/TiO2/PMMA/C device exhibited the lowest SET/RESET voltage, an ON/OFF ratio of ~101, a retention of ~104 s, and an endurance of ~102 cycles, underscoring the impact of PMMA placement on decreasing the switching threshold. These findings provide a novel strategy for designing next-generation NVM applications, in which the interfacial positioning role of polymers in optimizing ReRAM performance could be effectively understood.